The estimation of author program's efficiency of preparation Ukrainian rowing women team to the Olympic Games - 2012 - Dina Miftahutdinova (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to give the estimation of efficiency of the use of the authorial training program in setup time for the women's Ukraine rowing team representatives in the process of preparation to Olympic Games in London. Materials and Methods: 10 sportswomen of higher qualification, that are included to Ukraine rowing team, are participated in research. For the estimation of general and special physical preparedness the standard test and rowing ergometre Concept-2 are used. Results: the end of the preparatory period was observed significant improvement significant general and special physical fitness athletes surveyed, and their deviation from the model performance dropped to 5-7%. Conclusions: the high efficiency of the author training program for sportswomen of Ukrainian rowing team are testified and they became the Olympic champions in London.